Posted by **cynthia** on Tuesday, February 28, 2012 at 1:57am.

1. f(x)=√5x+6, find f'(x)

2. f(x)=√4x^2+3x+4, find f'(x).

i got stuck.

f(x)=√5x+6=(5x+6)^1/2

f'(x)= 1/2(5x+6)^-3/2*(5).

- Calculus AP need help! -
**Steve**, Tuesday, February 28, 2012 at 11:09am
Almost. How did you get from ^1/2 to ^-3/2? 1/2 - 1 = -1/2.

f = (5x+6)^(1/2)

use the power rule and chain rule:

f' = 1/2 * (5x+6)^(-1/2) * 5 = 5/(2√(5x+6))

f = √(4x^2+3x+4)^(1/2)

f' = 1/2 * (4x^2+3x+4)^-1/2) * (8x+3) = (8x+3)/(2√(4x^2+3x+4))

- Calculus AP need help! -
**cynthia**, Tuesday, February 28, 2012 at 2:23pm
oops.. i thought 1/2 to -3/2. now i understand. thanks

## Answer this Question

## Related Questions

- Math - Find an equation of the line that bisects the obtuse angles formed by the...
- Algebra - How would i complete these problems? 1. (√6mn)^5 2. ^3√16x...
- maths - I will be thankfull to you if you help me to solve the below problem: 6...
- algebra 1 help - simplifying square roots 1) find volume of this prism? v=bwh b...
- Math - I need someone to check my homework answers. I don't really know this ...
- Algebra 2 - Can someone help me with this radical expression please? The problem...
- Algebra - Simplify the expressions and solve the equations 1. 2√3 - √...
- Algebra Work Check - 1. 5√6 * 1/6√216 5/6 * √1296 5/6 * √...
- Algebra 2 Answer Check - Simplify by rationalizing each denominator. 1. 2/√...
- algebra 1 - alright i have a few questions if its ok..? Simplify: 1. -2√(...

More Related Questions